Equilibrium Passive Sampling of POP in Lipid-Rich and Lean Fish Tissue: Quality Control Using Performance Reference Compounds - Rusina, Tatsiana P; Carlsson, Pernilla; Vrana, Branislav; Smedes, Foppe (Environmental science & technology, 2017)
Passive sampling is widely used to measure levels of contaminants in various environmental matrices, including fish tissue. Equilibrium passive sampling (EPS) of persistent organic pollutants (POP) in fish tissue has been hitherto limited to application in lipid-rich tissue. We tested several exposure methods to extend EPS applicability to lean tissue. Thin-film polydimethylsiloxane (PDMS) passive samplers were exposed statically to intact fillet and fish homogenate and dynamically by rolling with cut fillet cubes. The release of performance reference compounds (PRC) dosed to passive samplers prior to exposure was used to monitor the exchange process. The sampler-tissue exchange was isotropic, and PRC were shown to be good indicators of sampler-tissue equilibration status. The dynamic exposures demonstrated equilibrium attainment in less than 2 days for all three tested fish species, including lean fish containing 1% lipid. Lipid-based concentrations derived from EPS were in good agreement with lipid-normalized concentrations obtained using conventional solvent extraction. The developed in-tissue EPS method is robust and has potential for application in chemical monitoring of biota and bioaccumulation studies.
Keywords: Lipids; Water Pollutants, Chemical; Environmental Monitoring; monitorování životního prostředí; Fishes; lipidy; Animals; Quality Control; zvířata; řízení kvality; ryby; chemické látky znečišťující vodu